Medical risk in dental patients according to the ASA classification - Maribel de las Mercedes Bastarrechea Milián; Agustín Rodríguez Soto; Denia Morales Navarro (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: To carry out a dental treatment without compromising the systemic condition has been the aim of several studies. Among them, there is the determination of the medical risk according to ASA classification in patients attending the dental consultation, which has not been reported in Cuba. Objective: To identify the medical history and to determine the ASA as a predictor of medical risk in patients attending the dental consultation. Material and Method: The CROMEC questionnaire was applied to 30 patients that requested dental consultation for the first time. Age, sex, medical history and medications were taken into account to finally determine the ASA classification of the patients. Results: The 60-year-old age group or over prevailed with 53,3 % and, within this group, the female sex with 60 %. Besides, 63,3 % of patients studied had medical history, predominating the hypertensive patients with 56,6 %, followed by those suffering from diabetes mellitus with 36,6%. The most frequently used medications were the antihypertensive ones with 32%, followed by those used for diabetes mellitus with 20 %. In total, 43,3 % of patients were included in the ASA II classification.  Conclusions: More than half of the patients studied presented medical history, being arterial hypertension and diabetes mellitus in correspondence with the greater use of antihypertensive and diabetes mellitus medications the most frequent ones. Most of the patients corresponded with ASA II classification and mild systemic illness, indicating dental treatment with modifications.